China's emerging partnership network: what, who, where, when and why. Issue 2 (15th July 2019) - Li, Quan; Ye, Min
Abstract : Purpose: The purpose of this paper is to explore and test the motivation behind the evolution of China's vast network of partnerships around the globe since the end of the Cold War. Design/methodology/approach: After combing through 24 types of partnerships with 78 countries, the authors empirically tested four hypotheses using data from Correlates of War and World Bank. Findings: The analysis indicates that China's choice to build such an elaborate network is not random. On the contrary, it is largely determined by three factors: the need to counter the US pressure; the necessity of maintaining peace and stability along its borders and achieving the long-term goal of modernization. Originality/value: The research is among the first attempts to comprehensively test the possible motivations behind China's partnership building efforts and provides a stepping stone for analyzing this important aspect of China's foreign policy.